1999
DOI: 10.1152/ajpgi.1999.276.4.g915
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of RhoA and its interaction with protein kinase C and Src in CCK-stimulated pancreatic acini

Abstract: We evaluated intracellular pathways responsible for the activation of the small GTP-binding protein Rho p21 in rat pancreatic acini. Intact acini were incubated with or without CCK and carbachol, and Triton X-100-soluble and crude microsomes were used for Western immunoblotting. When a RhoA-specific antibody was used, a single band at the location of 21 kDa was detected. CCK (10 pM–10 nM) and carbachol (0.1–100 μM) dose dependently increased the amount of immunodetectable RhoA with a peak increase occurring at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 28 publications
4
30
0
Order By: Relevance
“…Because Rho possesses the forming homology (FH) 1 domain, which is enriched in proline, this domain may directly interact with the Src homology (SH) 3 domain of Src. 47 To our knowledge, this is the first report to demonstrate that the induction of RhoA activity by IL-6 was mediated by Src phosphorylation and then, IL-6 may act through Src phosphorylation on cancer cells to promote and accelerate cancer cell migration and invasion. Although more IL-6 production was noted in clone 5 ( Fig.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Because Rho possesses the forming homology (FH) 1 domain, which is enriched in proline, this domain may directly interact with the Src homology (SH) 3 domain of Src. 47 To our knowledge, this is the first report to demonstrate that the induction of RhoA activity by IL-6 was mediated by Src phosphorylation and then, IL-6 may act through Src phosphorylation on cancer cells to promote and accelerate cancer cell migration and invasion. Although more IL-6 production was noted in clone 5 ( Fig.…”
Section: Discussionmentioning
confidence: 76%
“…46 Besides, another study also found that RhoA was coimmunoprecipitated with Src, so RhoA may interact with Src. 47 Because Rho does not possess Src homology domains, this interaction may be mediated by Rho-GAP, which possesses Src homology domains. Indeed, p190…”
Section: Discussionmentioning
confidence: 99%
“…For example, the interaction between PKC and Rho regulates enzyme secretion in pancreatic acini (64). In epithelial and endothelial cells, treatment with C3 toxin prevented PKC translocation and activation (65).…”
Section: Discussionmentioning
confidence: 99%
“…Rho may also be involved in this pathway, since inhibition of rhoA with C3 transferase induced disassembly of the cytoskeletal actin, including the perijunctional actin myosin ring, and increased tight junction permeability (Nusrat et al, 1995). Furthermore, U73122 was found to inhibit Rho activity (Nozu et al, 1999).…”
Section: Discussionmentioning
confidence: 99%